Біометрична характеристика листків і плодів генотипів Cornus officinalis Siebold et Zucc. в Національному ботанічному саду ім. М.М. Гришка НАН України - Klymenko, S.V.; Ilyinska, A.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2020)
In the context of global climate change, the current strategy of agroeconomics focuses on the introduction of unique plant species and the selection of new commercially important cultivars adapted to the dramatic weather changes. Cornus officinalis (Cornaceae) has Chinese origin, its reintroduction at the M.M. Gryshko National Botanical Garden, National Academy of Sciences of Ukraine started in 1993. The objectives of this research were: to investigate the biometric parameters of fruits and leaves of C. officinalis genotypes, C. officinalis × C. mas hybrid ‘Etude’ and genotype from the grafting C. officinalis on C. mas under cultivation in the M.M. Gryshko National Botanical Garden, National Academy of Sciences of Ukraine, and to determine the degree of adaptation of C. officinalis to the climatic conditions of Ukraine (in particular, Right-Bank Forest Steppe) for selection of promising genotypes for further breeding work. Material and methods. We used: a) 26-year-old maternal plant obtained from a two-year-old seedling in 1993 received from the nursery “Northwoods Wholesale Nursery” Mollala (Oregon, USA), where it was grown as an ornamental plant; b) seedlings of the maternal plant; c) cultivar Etude, which is an artificial hybrid from crossing C. officinalis × C. mas; and d) genotype obtained from grafting C. officinalis on C. mas. In our experiment, the maternal plant is indicated as G-01, while other plants – as G-02–G-08 genotypes. We determined the biometric parameters of the fruit (length, diameter, and weight), endocarp (length, diameter, and weight), pedicel (length and thickness), leaf blade (length, width, and the number of lateral veins) and petiole (length, width, and thickness). We examined the dynamics of fruit and endocarp formation during the season (genotypes G-01–G-03 and G-05) and compared the biometric characteristics of the fruit of genotypes G-01–G-05 from crops of two years, 2010 and 2018, which were most favorable in weather conditions. We have processed quantitative data in the PAST 2.10 software. The differences between the samples were estimated using the Tukey-Kramer test. The degree of variability was determined by the coefficient of variation. To assess the level of variability, we used the classification of Mamaev (1975). Results. We have found that the largest fruits in 2010 were observed in the genotype G-01 and the smallest – in the genotype G-03. The coefficient of variation of the linear parameters of the fruit and endocarp was in the range 5.7–10.1 %; the level of variability was very low or low. The variability of fruit weight and endocarp was high; the coefficient of variation was from 7.0 up to 28.3 %. The amplitude of the linear parameters of the leaf was wide (coefficient of variation was from 9.8 to 31.0 %). The cultivar Etude differed from other C. officinalis genotypes in size and weight of (M = 1800 mg, max = 2400 mg) and a much wider amplitude of variation in the length (17.9–22.6 vs. 14.3–18.2 mm) of the fruit. The largest leaves were in the genotypes G-08 and G-01, and the smallest – in the genotype G-02. The cultivar Etude did not differ so much by the mean leaf morphometric indices and number of veins, but it demonstrated one of the broadest leaf blades (51.5 mm). Conclusions. The data obtained in this study is important for the commercial use of C. officinalis and the cultivar Etude as food and medicinal plant, as well as for breeding in climatic conditions of Ukraine and analysis of hybridization features in the genus Cornus in general.